Archive Footage in New Programmes - Bryant, Steve (VIEW Journal of European Television History and Culture, 2015)
Archivists have traditionally been concerned about what they have seen as incorrect usage of archival footage in new documentaries, but changing technologies and programme-making conventions have made this inevitable. This paper considers aspects of these changes, focussing particularly on the issue of how the introduction of widescren television affected and continues to affect the aspect ratios in which archival materials are presented, using examples from recent and contemporary television documentaries from Britain and the USA.